Potential allelopathic effects of Suregada multiflorum and the influence of soil type on its residue's efficacy - CHAMROON LAOSINWATTANA; CHANINAT BOONLEOM; MONTINEE TEERARAK; SOMPOP THITAVASANTA; PATCHANEE CHAROENYING (My University, 2010)
This experiment was conducted to determine the potential allelopathic effects of the aqueous extracts and dried leaf powder of Suregada multiflorum and to find the herbicidal effects of its granule on the weed species, barnyardgrass ( Echinochloa crus‐galli ) and slender amaranth ( Amaranthus viridis ), in various growth media (germination paper, sand, and soil). Observations in this study demonstrated that the potential and magnitude of their inhibitory effects varied among the plant parts. The leaves and branches possessed the strongest inhibition levels, followed by the bark. The aqueous extract from the leaves of S. multiflorum had a remarkably stronger inhibitory effect on the germination and growth of slender amaranth, compared with barnyardgrass; when applied at the concentration of 100 g L –1 , it completely inhibited the germination and initial seedling growth of slender amaranth. In addition, all the treatments of the dried leaf powder had stronger inhibition effects than the aqueous extract. Interestingly, the inhibitory effects of the dried leaf granule of S. multiflorum were stronger than the effects of the dried leaf powder at equal rates. The degree of inhibitory effect of the S. multiflorum granule, applied in various growing media, can be classified in order of decreasing inhibition as germination paper = sand > clay soil. The present study indicates that the S. multiflorum granule product that was developed in this research has the potential to provide a powerful organic herbicide for controlling slender amaranth.
Keywords: Allelopathy; Allelopathy and phytotoxic interactions